Machos de Rhamdia quelen alimentados com dieta contendo glicerina bruta apresentam melhora na qualidade seminal e alterações bioquímicas no sangue - Oliveira, Eder José de (2018)
The objective of this study was to evaluate the effects of the inclusion of crude glycerin on the diet of jundia (Rhamdia quelen) on growth, seminal and spermatic characteristics, blood parameters and tissue composition. The animals were distributed in completely randomized experimental design, consisting of five treatments and four replications. The treatments consisted of isoproteic and isoenergetic rations containing 30 % of digestible protein (PD) and 3.000 kcal of digestible energy (ED).kg-1 of ration and five levels of inclusion of crude glycerin in the proportions of 0, 4, 8, 12 and 16 %. 12 months after the beginning of the experiment, the reproductive parameters of the males were evaluated, as well as the integrity of the sperm DNA by the comet assay method. Eight males from each experimental unit were submitted to blood collection for quantification of levels of calcium, triglycerides, plasma glucose, total proteins, aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, total cholesterol erythrocyte DNA integrity. Afterwards, all males were submitted to euthanasia for dissection and individual measurement of weights of the liver, gonads and viscera to evaluate the zootechnical, somatic parameters and analysis of organ and tissue centesimal composition. There was an increase (p < 0,05) in the concentration of spermatozoa in the animals fed the rations containing the highest level of crude glycerin. The other seminal and sperm parameters were not influenced. Among the blood parameters, levels of total cholesterol, total protein and calcium were influenced (p < 0,05), total cholesterol and total protein presented higher values with 8 % inclusion of crude glycerin in the diet, whereas calcium decreased with 16 % inclusion of crude glycerin. Zootechnical performance was not influenced. In the evaluation of centesimal composition, there was influence (p < 0,05) on muscle dry matter, muscle ashes and crude protein of the muscle, viscera and gonads. Dry matter and muscle ashes, gross protein of the viscera and gonads increased the concentrations with the addition of crude glycerin in the rations, whereas the crude protein concentration of the muscle decreased with the presence of crude glycerin in the diets. Therefore, it is recommended to use this by-product as a substitute for maize in the diet of jundia breeders, since it does not present negative effects and still benefits their reproductive performance.